CD10 for the distinct differential diagnosis of basal cell carcinoma and benign tumours of cutaneous appendages originating from hair follicle - Sengul, Demet; Sengul, Ilker; Astarci, Muzeyyen Hesna; Ustun, Huseyin; Mocan, Gamze (Polish Journal of Pathology, 2010)
Aims : Differential diagnosis between the group of trichoadenoma, trichofolliculoma, trichoepithelioma, trichoblastoma and basal cell carcinoma has been creating some difficulties for the pathologist and the clinicians, particularly in the presence of small specimens. Material and methods : A total of 30 cases of benign tumours of cutaneous appendages originating from the hair follicle and 30 cases of basal cell carcinoma were retrieved from the archives deposited from 2004 to 2008. Results : The expression of CD10 in both tumours was graded from [0] to [2+] for each case. The immunoreactivity of CD10 was comparatively examined among the groups and each subgroup. The stromal CD10 immunopositivity of benign tumours of cutaneous appendages originating from the hair follicle was stronger than the other (p = 0.003) regarding both the numerical and the degree of expression. However, peripheral CD10 of basal cell carcinoma was stronger than the other for [1+] immunopositivity (p = 0.03). It was exact opposite for [2+] (p = 0.013). Besides, central CD10 immunopositivity and CD10 reactivity for the subgroups was not significant. Conclusions : CD10 may be very useful for the differential diagnosis between them particularly in the small and superficial biopsies and it may be even a life-saving method in some selected cases.